PERANCANGAN APLIKASI LAPORAN LABA RUGI MENGGUNAKAN METODE BERORIENTASI OBJEK - Vicky Yuzar Rachmat; Eko Retnadi; Rina Kurniawati (Institut Teknologi Garut, 2015)
The purpose of this study was to Designing Applications Income Statement CV. PAHLAWAN TOURS in support of the activities of the processing of financial transactions in the Finance section. With less well in the management and storage of data, resulting in the process of recording transactions that are not done correctly in the accounting. As a means to overcome the above problems, the authors create application programs using the income statement analysis and system development with object oriented methodology models Unified Approach (UA) raised by Ali Bahrami (1999), comprising the steps of Object Oriented Analysis (OOA) and Object Oriented Design (OOD) using Unified Modeling Language (UML) for modeling system requirements. Based on the analysis and design on the application income statement, can produce applications that aim to maximize every working processes and to support the activities of the particular financial transaction.